2016
DOI: 10.1080/02701960.2015.1079706
|View full text |Cite
|
Sign up to set email alerts
|

Walking a mile in another’s shoes: The impact of wearing an Age Suit

Abstract: The "Age Suit" described in this article was developed to enable future designers, business leaders, and engineers to experience navigating the world as many older adults must. Tools such as this Age Suit offer the opportunity to "walk a mile" in another's shoes to develop empathy that can result in better design of spaces, goods, and services to meet the needs of a rapidly growing older population. This work first examined, through a series of clinical tests, whether younger adults' physical capacities were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…The concept of using simulation suits is relatively new and is increasingly being examined as a learning tool for healthcare students (15,16,19), but use of simulation suits had not been studied in a randomized controlled cohort of pharmacy students. Our study found that the immersive aging simulation suit did not significantly improve participants' self-rated empathy levels compared to a polypharmacy workshop only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of using simulation suits is relatively new and is increasingly being examined as a learning tool for healthcare students (15,16,19), but use of simulation suits had not been studied in a randomized controlled cohort of pharmacy students. Our study found that the immersive aging simulation suit did not significantly improve participants' self-rated empathy levels compared to a polypharmacy workshop only.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, the authors noted that students gained a better understanding of the functional issues and social isolation that are associated with aging after using the aging suit. Lavallière et al similarly examined the use of an aging suit among younger adults (19) and found that they could relate better to the physical limitations and reduced performance associated with aging.…”
Section: Introductionmentioning
confidence: 99%
“…Ageing-suits are emerging as a promising addition to the simulation family because they have the unique ability to situate the learner as the "older person" and not just as the healthcare professional (Lavalliere et al, 2017). Ageing-suits are constructed to Relevance to clinical practice: Ageing-suits were identified as a worthwhile educational approach for aged care nurses to improve their specialised clinical practices with older people.…”
Section: Introductionmentioning
confidence: 99%
“…Educators implement a wide range of simulation modalities, for example standardised patients (actors), part‐task trainers or full‐body mannequins (Hegland et al., 2017; Meyer et al., 2014). The healthcare sector uses more advanced simulation modalities because they take advantage of the new technologies, particularly ageing‐suits (Evans, Lombardo, Belgeri, & Fontane, 2005; Halpin, 2015; Lavalliere et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation